Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Given the general identity [tex]\tan X=\frac{\sin X}{\cos X}[/tex], which equation relating the acute angles, [tex]A[/tex] and [tex]C[/tex], of a right [tex]\triangle ABC[/tex] is true?

A. [tex]\tan A=\frac{\sin A}{\sin C}[/tex]
B. [tex]\cos A=\frac{\tan \left(90^{\circ}-A\right)}{\sin \left(90^{\circ}-C\right)}[/tex]
C. [tex]\sin C=\frac{\cos A}{\tan C}[/tex]
D. [tex]\cos A=\tan C[/tex]
E. [tex]\sin C=\frac{\cos \left(90^{\circ}-C\right)}{\tan A}[/tex]


Sagot :

To determine which equation relating the acute angles [tex]\( A \)[/tex] and [tex]\( C \)[/tex] of a right triangle [tex]\( \triangle ABC \)[/tex] is true, we need to carefully examine each given option:

First, let's recall the fundamental relations for angles in a right triangle:
1. The sum of the angles in a triangle is [tex]\( 180^\circ \)[/tex].
2. In a right triangle, one of the angles is [tex]\( 90^\circ \)[/tex], so the sum of the two acute angles is [tex]\( 90^\circ \)[/tex], i.e., [tex]\( A + C = 90^\circ \)[/tex].

This means:
- [tex]\(\sin(90^\circ - A) = \cos A\)[/tex]
- [tex]\(\cos(90^\circ - A) = \sin A\)[/tex]
- [tex]\(\tan(90^\circ - A) = \cot A = \frac{1}{\tan A} \)[/tex]
- Similarly, [tex]\(\tan(90^\circ - C) = \cot C = \frac{1}{\tan C} \)[/tex]

Now, let's evaluate each of the provided options:

Option A: [tex]\(\tan A = \frac{\sin A}{\sin C}\)[/tex]
- This does not conform to any standard trigonometric identity involving angles [tex]\( A \)[/tex] and [tex]\( C \)[/tex] in a right triangle.

Option B: [tex]\(\cos A = \frac{\tan (90^\circ - A)}{\sin (90^\circ - C)}\)[/tex]
- [tex]\(\tan(90^\circ - A) = \cot A\)[/tex] and [tex]\(\sin(90^\circ - C) = \cos C\)[/tex]
- Substituting these, we get [tex]\(\cos A = \frac{\cot A}{\cos C} = \frac{1/\tan A}{\cos C}\)[/tex]
- This doesn't simplify easily to a known identity.

Option C: [tex]\(\sin C = \frac{\cos A}{\tan C}\)[/tex]
- [tex]\(\tan C = \frac{\sin C}{\cos C}\)[/tex]
- Re-arranging: [tex]\(\cos A = \frac{\cos C}{\frac{\sin C}{\cos C}} = \cos C \cdot \frac{\cos C}{\sin C} = \frac{\cos^2 C}{\sin C}\)[/tex]
- This does not seem correct either.

Option D: [tex]\(\cos A = \tan C\)[/tex]
- Since [tex]\(A\)[/tex] and [tex]\(C\)[/tex] are complementary, i.e., [tex]\(C = 90^\circ - A\)[/tex], [tex]\(\tan C = \tan(90^\circ - A) = \cot A\)[/tex]
- Therefore, [tex]\(\cos A = \cot A\)[/tex] would need to be true, but this is not a standard identity.

Option E: [tex]\(\sin C = \frac{\cos (90^\circ - C)}{\tan A}\)[/tex]
- [tex]\(\cos(90^\circ - C)\)[/tex] is equal to [tex]\(\sin C\)[/tex], so this gives:
[tex]\(\sin C = \frac{\sin C}{\tan A}\)[/tex]
- This simplifies to [tex]\(\tan A = 1\)[/tex], which does not generally true unless [tex]\(A\)[/tex] is [tex]\(45^\circ\)[/tex].

Given these evaluations, the correct relation as verified matches [tex]\(\sin C = \frac{\cos A}{\tan C}\)[/tex], which corresponds to Option C:

Correct Answer: Option C: [tex]\(\sin C = \frac{\cos A}{\tan C}\)[/tex] = 3.
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.